Análise da Estratégia Fenodinâmica de Cistus salvifolius em Três Locais Distintos (Pinhal de Leiria, Cabeção e Odemira) (Silva Lusitana, 2002)
We describe the phenomorphological strategy of Cistus salvifolius found in pine woods of the Leiria region and in cork oak woodlands of Alentejo (Cabeção and Odemira north and Odemira south). An analysis is made of the evolution of the biological cycle as a function of climatic changes